Sánchez-Díez, Alicia. Cartilla para catalogar. Madrid: Fundación Universitaria Española, 2024 - Rodríguez-Romero, Ana-María; Lázaro-Rodríguez, Pedro; Sánchez-Díez, Alicia (Revista de Investigación sobre Bibliotecas, Educación y Sociedad, 2025)
Reseña sin resumen